Computational fluid dynamics simulation on the heat sink performance of a graphics processing unit thermal management - Zambri Harun,; Ng, Jie Suang; W. M. Faizal W. Mahmood,; Mahir Faris Abdullah,; Eslam Reda Lotfy, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The article focuses on the numerical investigation of temperature distribution in a central processing units (CPU) case with different time interval such as t = 100 s, 200 s, 300 s, 400 s, 500 s. Heat sink performance of a graphics processing unit (GPU) thermal management and impacts of different shape and velocity on the thermal performance are considered. In this study, three heat sink models are designed (A, B, and C) based on the volume area of heat sink. This study emphasizes the heat transfer phenomena caused by a GPU in a computer case in both steady state and transient state. A CFD software STAR – CCM + is used to carry out to study the fluid flow and heat transfer simulation of graphics card heat sink in a computer case and the same time an enhanced method of reducing the temperature of GPU is proposed. The results show that heat sink B with the least volume area, has the fastest rate of heat exchange followed by heat sink C and heat sink A. Likewise, the result indicates an inverse relationship between the volume and the total surface of the heat sink and the final temperature of the graphics card chip. As the total volume and surface of the heat sink increases, the rate of heat transfer increases via faster rate of conduction between graphics card chip to heat sink meanwhile the cooling of the heat sink is aided by wind inlet via convection.